2017
DOI: 10.1097/mib.0000000000001187
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal Manifestations Are Common in Obese Patients with Crohnʼs Disease

Abstract: Most patients were overweight or obese, which correlates with national population trends. Our data suggest disease location plays a role in weight modulation in patients with CD. Increased extraintestinal manifestations in patients with high BMI suggests that the chronic inflammation associated with obesity may play a role in extraintestinal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…In their retrospective cohort study, Malik et al [48] found that obese CD patients were approximately 2.5 times more likely to present a poor surgical outcome than those who were nonobese. In a more recent, retrospective study of 209 adult patients with CD, Singla et al [49] observed that patients with a higher BMI were more likely to present with extraintestinal manifestations. Pavelock et al [50], in their retrospective observational study on IBD patients (63% CD and 37% UC), found that obesity negatively influences the clinical course of IBD and may increase the burden of disease and treatment.…”
Section: Effect Of Obesity On the Course Of Ibdmentioning
confidence: 99%
“…In their retrospective cohort study, Malik et al [48] found that obese CD patients were approximately 2.5 times more likely to present a poor surgical outcome than those who were nonobese. In a more recent, retrospective study of 209 adult patients with CD, Singla et al [49] observed that patients with a higher BMI were more likely to present with extraintestinal manifestations. Pavelock et al [50], in their retrospective observational study on IBD patients (63% CD and 37% UC), found that obesity negatively influences the clinical course of IBD and may increase the burden of disease and treatment.…”
Section: Effect Of Obesity On the Course Of Ibdmentioning
confidence: 99%
“…(1) Obesity has been variably associated with IBD phenotype, with some studies suggesting milder disease and others suggesting lower prevalence of remission in cross-sectional studies. (1)(2)(3)(4) There are conflicting data on how obesity may impact outcomes in patients with IBD, with some studies showing inferior quality of life and higher healthcare utilization, whereas others showing no significant difference in the risk of IBD-related surgery, hospitalization or emergency department use in obese vs. overweight vs. normal BMI adults. (4)(5)(6)(7)(8) Obesity has also been shown to negatively impact response to biologic therapy in patients with ulcerative colitis (UC) and other immune-mediated diseases, but this observation has been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…In crosssectional studies, obesity has not been consistently associated with an increased prevalence of complicated CD phenotype (perianal disease, penetrating, or stricturing phenotype). 1,2,8 Longitudinal studies have shown variable impact of obesity on natural history in patients with IBD. Seminerio et al observed that obese patients, particularly those with class II or III obesity, had lower scores on quality-of-life metrics and higher serum inflammatory markers, as compared with nonobese patients, but there was no meaningful difference in the risk of surgery or healthcare utilization.…”
Section: Introductionmentioning
confidence: 99%